P44 Liver ultrasound practice is heterogenous and failing to highlight clinically significant liver disease. (20th September 2022) - Leith, Damien; Barclay, Stephen; Burgul, Raj; Hayes, Peter C; Heydtmann, Mathis; Stout, Morag; Patel, Dilip; Leithead, Joanna A
Abstract : Liver ultrasound [US] is recommended in the initial investigation of patients with abnormal liver function tests [LFT] (BSG guidelines, Newsome et al 2017); however there is a paucity of guidance for US practice in this setting with implications for disease identification. Our aim was to review terminology and practice of the outpatient "abnormal LFT" US, and its efficacy in the risk stratification of liver disease. Methods: A Scotland wide service evaluation on behalf of the Scottish Society of Gastroenterology in collaboration with the Scottish Radiological Society of all adult outpatient US scans performed for the indication "abnormal LFTs" 04–17/10/21. Results: 515 US scans were reviewed from 11/14 Health Boards. 69% of scans were requested by Primary Care; 78% were performed by a Radiographer. There was significant variability in descriptive terminology and parameters reported – this variability was not influenced by hospital type, requesting information or scan findings; and instead related to teaching deanery – on adjusted analyses the North (p<0.001, p<0.001) and West deaneries (p<0.001, p=0.002) were less likely to describe the liver edge and portal vein. Of the 281 scans reporting "fatty liver", incomplete information was provided to risk stratify in 76%: the liver edge, absolute spleen size and presence/absence of ascites were described in only 40%, 16% and 55%, respectively. Overall, 45 scans (9%) reported characteristics very suggestive of cirrhosis, but the terminology "cirrhosis" was mentioned in only 5 of these scan reports (11%) and referral to Gastroenterology recommended in only 1 – implying at least 884 missed opportunities to diagnose cirrhosis in Scotland per year. Conclusions: Current liver ultrasound practice is heterogenous and failing to highlight clinically significant disease during the work up of abnormal LFTs. Our results emphasise the need for standardisation of reporting and referral pathways.